Foaming characteristics of ultrasound-treated whey protein solutions and their use as aerating agent in angel cake manufacture - Tan, Mei Ching (2014)
The effect of ultrasound on foam properties of whey protein and its application on mixed batter and baked cakes were studied. Full factorial design was used to study the aeration and rheological properties of whey protein foam before and after its suspension was treated with ultrasound. This involved three factors, i.e. protein concentration of 10%, 15% and 20%, ultrasound amplitude of 20%, 40% and 60%, and sonication time of 5, 15 and 25 minutes. The increase of ultrasound amplitude and sonication time gave positive effects to overall quality of foam measured in terms of aeration and rheological properties. At the highest amplitude of 60% and longest sonication time of 25 minutes, foam from 20% concentration showed greatest increase in stability (35%), consistency index (18%), storage modulus (17%), loss modulus (26%) and viscosity (21%). The ANOVA results showed that protein concentration, ultrasound amplitude and sonication time gave significant effects (P < 0.0005) on all the aeration and rheological properties of whey protein foam. A general master-curve relating shear stress or viscosity of foam at any protein concentration, and treated at any ultrasound amplitude and sonication time at the desired shear rate was obtained with a high coefficient of determination, R 2 = 0.9959. Cake batter mixed with ultrasound treated foam at 60% amplitude for 25 minutes showed decreased density (5%), increased consistency index (57%), storage modulus (33%), loss modulus (21%) and viscosity (31%), resulting in final cake product with increased volume (18%), decreased density (18%), ahrdness (65%), chewiness (64%), gumminess (64%) and resilience (3%) when compared with control cake using untreated whey protein. The appearances of cake formulated with ultrasound treated whey protein were comparable to those from egg white protein in terms of volume and density. In addition, it gave better textural properties of lower hardness, gumminess and chewiness. The X-ray tomography and X-ray microtomography techniques were able to show the significant effect of ultrasound treatment on aerated foam and cakes through 2D and 3D images and bubbles size distribution analyses. Both techniques proved that the quantity of microbubbles with size range of 0 to 0.0025 mm3 in the foam system had increased 46% while microbubbles with size range of 0.01 to 0.1 mm2 in cake system had increased 38% after ultrasound treatment at 60% amplitude and 25 minutes sonication of protein suspension before foaming. The relationships of aeration, rheological and textural properties between foam, batter and cake were found to have high correlation coefficients. In conclusion, ultrasound treatment can improve the functional properties of whey protein foam, and the treated whey protein foam can effectively replace egg white in the making of high quality egg free angel food cakes.